MANAJEMEN KRISIS PUBLIC RELATIONS PT. HERO SUPERMARKET PADA PENUTUPAN GERAI GIANT INDONESIA - Amarilia Shinta; K. Y. S Putri (Universitas Teuku Umar, 2022)
Losses and profits are common things that happen to big companies. But it will be a problem if the company often suffers losses. Losses experienced by the company if not handled properly can affect other aspects. The crisis was due to losses that did not better will make the company have to take certain steps, which ultimately had an impact on the fate of the company. Retail Giant is one of the many retailers that have closed due to company losses. Giant which is a subsidiary of PT Hero Supermarket (HERO Group) decided to close all outlets in July 2021. The issue that emerged was that Giant had done Termination of Employment and closed dozens of outlets in various locations. The purpose of this study was to find out how crisis management was carried out by public relations at PT Hero Supermarket at the closing of the Giant Indonesia outlet. The theory used in this research is the crisis management theory. The method used is a qualitative research method with a descriptive analysis approach and content analysis. The results obtained by researchers in this study are PT Hero Supermarket's public relations divide the crisis into three parts; pre-crisis, crisis phase, and post-crisis. In the pre-crisis phase, the company tries to convince the public that the outstanding issues can still be resolved, in the crisis phase the company takes steps to permanently close the Giant stores, and in the post-crisis stage the company guarantees that employee rights are fulfilled.